Posterior Reversible Encephalopathy Syndrome (PRES) in a Patient Treated with a Novel Combination Treatment with Anti PDL1 Antibody (Durvalumab) and VEGFR2 Antibody (Ramucirumab) - Perez, Jaime Rubio; Hernández, Roberto; Lage, Yolanda; Rupérez, Ana Belén; Ruiz, Eva; Hernández, Tatiana; Doger, Bernard; Garcia-Foncillas, Jesús; Moreno</p, Víctor (Archives of Clinical and Medical Case Reports, 2020)
Background: The use of novel agents such as checkpoint inhibitors and the combination with targeted therapies has been increasing exponentially in the last years. Because of this the toxicity profile has been changed and uncommon syndromes are more frequent nowadays. PRES is a rare syndrome that causes neurological acute symptoms such as bradypsychia, seizure and even irreversible blindness if treatment is not initiated soon enough. It has been related to multiple diseases and conditions including with chemotherapy drug combinations and with the use of new oncological drugs. The incidence will probably increase in the net years, so we should describe these cases and develop clinical guidelines for the diagnosis and management of PRES. Case Presentation: Here we present a 64-year-old woman with a stage IV adenocarcinoma of the lung that developed PRES during treatment with a combination of ramucirumab, a monoclonal antibody against vascular endothelial growth factor 2 (VEGFR2), and durvalumab, an antagonist of programmed death-ligand 1 (PD-L1). She developed the syndrome with complete remission of symptoms after two weeks, requiring an adjustment of antihypertensive medications. Conclusions: The clinical importance of this case lies in the fact that despite its low incidence, we should be aware of these potential toxicities with the increasing use of novel agents in different combinatorial strategies, mainly in patients with other comorbidities. An early diagnosis is crucial since the prognosis depends upon it, decreasing the risk of permanent neurological damage and even death.